Optimization of mycodextran production from efficient fungal in submerged culture - Phichamon Noisuwan (2018)
© 2017, Chiang Mai University. All rights reserved. Mycodextran production from various strains of fungal was reported using modified media composed of different carbon sources from agricultural wastes, grain extracts and a nigeran production (NP) medium. Aspergillus japonicus IFO 4337 had the highest yield of 0.25 g/l when cultured in NP medium and incubated at 28°C with shaking (120 rpm) for 14 days. Optimum medium components and culture conditions for mycodextran production in a shaking flask culture consisted of (% w/v) 3% glucose, 1% NH4NO3, and pH 5, incubated at 28°C for 7 days, and the highest mycodextran yield of 0.67 g/l. The brown-rice extract and coconut water were the optimal modified media for producing mycodextran and yielded 2.30 and 1.23 g/l, respectively, when incubated at 28°C, 120 rpm for 7 days. Static liquid culturing methods can reduce costs and had 8.3 fold higher yields compared to the shake flask culture. The Plackett-Burman design (PBD) was applied for evaluation of different medium component for mycodextran production by Aspergillus japonicus IFO 4337. Only NH4NO3is the most effective component with positive significance are selected for further optimization by response surface methodology (RSM).